1962
DOI: 10.1152/ajplegacy.1962.202.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sympathectomy on pulmonary embolism-induced lung edema

Abstract: A localized pulmonary infarction was produced by injecting a starch suspension into the pulmonary artery wedge position of one lung lobe in pentobarbitalized dogs, and the effect of bilateral surgical removal of the sympathetic chain was determined. Edema is significantly inhibited in ipsilateral and contralateral lung lobes of sympathectomized dogs. It is concluded that the sympathetic nervous system plays a major role as an efferent path in reflex production of pulmonary edema by starch emboli in the dog. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A few cases and our data indicated that a significant decrease in PVR was induced by the administration of vasodilators 16 , suggesting that increased pulmonary vascular tone may also be an important contributing factor in increasing PVR. The pathogenesis of this increased pulmonary vascular tone was unknown; hypoxic vasoconstriction, neurohormonal activation, and endothelial cell dysfunction may play a role 17,18,19 . Our data suggested that 9 patients with PH due to PA presented with hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases and our data indicated that a significant decrease in PVR was induced by the administration of vasodilators 16 , suggesting that increased pulmonary vascular tone may also be an important contributing factor in increasing PVR. The pathogenesis of this increased pulmonary vascular tone was unknown; hypoxic vasoconstriction, neurohormonal activation, and endothelial cell dysfunction may play a role 17,18,19 . Our data suggested that 9 patients with PH due to PA presented with hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic nervous system may be important in maintaining basal pulmonary tone, primarily through its activation of α 1 adrenoreceptors. 101,102 Sympathetic nervous input may increase and bring about an increase in pulmonary vasoconstriction under pathophysiologic conditions such as systemic hypotension, pulmonary embolism, neurogenic pulmonary edema, or reperfusion injury. [102][103][104][105][106] PARASYMPATHETIC INNERVATION.…”
Section: Neural Modulation Of Pulmonary Vascular Tonementioning
confidence: 99%
“…101,102 Sympathetic nervous input may increase and bring about an increase in pulmonary vasoconstriction under pathophysiologic conditions such as systemic hypotension, pulmonary embolism, neurogenic pulmonary edema, or reperfusion injury. [102][103][104][105][106] PARASYMPATHETIC INNERVATION. The pulmonary circulation also receives parasympathetic nervous system input, although it appears to have a less influential role on vascular tone than does the sympathetic system.…”
Section: Neural Modulation Of Pulmonary Vascular Tonementioning
confidence: 99%